Close to Home, One at a Time, Not in My Backyard: Individualism and the Mantras of Depoliticization in US Reform Discourses - Olga Thierbach-McLean (European Journal of American Studies)
The U.S. has a vibrant history of civic activism fueled by a strong individualistic tradition. But while stimulating critical views of the status quo, the individualist mindset has simultaneously acted as a brake on the democratic imagination by promoting the cultural narrative according to which meaningful social change can ultimately only occur by transforming one’s own private environment. This tendency finds expression in popular reform slogans, also including modern cyber-activism which – despite its global reach – shows a disposition to get absorbed in insular pet projects. It also plays a vital, jet largely unacknowledged role in America’s struggle with gun violence.